LITERASI MEDIA DIGITAL PADA PENGGUNAAN GADGET (Studi Deskriptif Penggunaan Gadget Pada Siswa SMK Broadcasting Bina Creative Medan Yang Berdampak Pada Pergeseran Nilai Kearifan Lokal) - Tonna Balya; Sri Pratiwi; Reza Prabudi (Universitas Medan Area, 2018)
The generation of digital children from birth was referred to as Digital native, at the same times people who was born at the first media age were referred to as digital immigrants. There are differences in thinking and how to use his mind between these two generations when processing information, the emergence of a new culture due to the use of digital media encourages changes in values in local culture. The general objective to be achieved in this study is to increase the awareness of teenagers that new cultures born as a result of new technological developments must be able to be balanced by having the awareness and ability to filter the new culture and still maintain the cultural values that have been inherited from ancestors as a form of one characteristic nations have many positive values. The method used in this study was a qualitative method with descriptive analysis techniques, PRA (Participatory Rural Appraisal) and SWOT. The results of this research mention that; ability, and understanding of students, parents, and educators about how technology changes learning, playing, community then an understanding of the importance of critical discussion on technological development to the stages of new media literacy that should be carried out is still in its early stages (just know it) and not yet applied.